2022
DOI: 10.1108/jbim-02-2022-0066
|View full text |Cite
|
Sign up to set email alerts
|

Towards dissemination, detection and combating misinformation on social media: a literature review

Abstract: Purpose Social media is becoming a hub of fake content, be it political news, product reviews, business promotion or any other sociocultural event. This study aims to provide a comprehensive review of the emerging literature to advance an understanding of misinformation on social media platforms, which is a growing concern these days. Design/methodology/approach The authors curate and synthesize the dispersed knowledge about misinformation on social media by conducting a systematic literature review based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 87 publications
(124 reference statements)
0
2
0
Order By: Relevance
“…They revealed that a positive and significant association was consistently found in relation to problematic Facebook use (PFU), but the consistency varied when all social media platforms were treated as one category. Within the realm of marketing research, Kaur and Gupta (2023) gathered scattered findings in studies concerning misinformation on social media through a systematic literature review and offered insights into the factors influencing the spread of misinformation on social media, as well as strategies for detection and mitigation. In the domain of epidemiology, Tang et al (2018) reviewed research pertaining to emerging infectious diseases (EIDs) and social media, and revealed that while the volume of studies on the topic is increasing, there is still a need to enhance theoretical underpinnings and address methodological shortcomings.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They revealed that a positive and significant association was consistently found in relation to problematic Facebook use (PFU), but the consistency varied when all social media platforms were treated as one category. Within the realm of marketing research, Kaur and Gupta (2023) gathered scattered findings in studies concerning misinformation on social media through a systematic literature review and offered insights into the factors influencing the spread of misinformation on social media, as well as strategies for detection and mitigation. In the domain of epidemiology, Tang et al (2018) reviewed research pertaining to emerging infectious diseases (EIDs) and social media, and revealed that while the volume of studies on the topic is increasing, there is still a need to enhance theoretical underpinnings and address methodological shortcomings.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the same study, the authors likewise observed misinformation to be most prevalent on social networking website Twitter-the platform where data for our study originated; however, all commonly used social networking websites are also prone to misinformation risk. Recommendations to counter misinformation risk on social media are mixed [46][47][48]. However, previous research suggests that to address misinformation effectively, all angles of misinformation risk and spread must be considered, including message-related, source-related, receiver-related, and context-related factors [49].…”
Section: Beyond Our Findings: Recommendations For Social Media Survei...mentioning
confidence: 99%